Effect of oral antihypertensive drugs on biochemical dosages in the elderly - Maria Elizana Martins de Meneses Carvalho; Eucário Leite Monteiro Alves; Maria do Carmo de Carvalho e Martins (Rev Rene)
Objective: to compare serum levels of uric acid, glucose, potassium and sodium in elderly users and non-users of oral antihypertensive drugs. Methods: observational, case-control study, including 232 elderly people with mean age 68.9 ± 7.4 years, of which 116 use and 116 do not use oral antihypertensive drugs, of both genders, non-diabetic and with no renal disease. After venous blood collection, glucose and uric acid were measured by colorimetric method; and sodium and potassium by the ion-selective electrode method. Results: there was an association between use of antihypertensive drugs and elevations in serum uric acid levels (p=0.040). And, among the classes, diuretic drugs demonstrated in this study relation with changes in uric acid levels (p=0.02) when compared to the other classes. Conclusion: the use of antihypertensive drugs, especially diuretics, has been associated with an increase in serum uric acid levels in hypertensive users of oral antihypertensive drugs.